2010
DOI: 10.1177/1947601910388030
|View full text |Cite
|
Sign up to set email alerts
|

MET Inhibition Results in DNA Breaks and Synergistically Sensitizes Tumor Cells to DNA-Damaging Agents Potentially by Breaching a Damage-Induced Checkpoint Arrest

Abstract: While recent studies implicate that signaling through the receptor tyrosine kinase MET protects cancer cells from DNA damage, molecular events linking MET to the DNA damage response machinery are largely unknown. Here, we studied the impact of MET inhibition by the small molecule PHA665752 on cytotoxicity induced by DNA-damaging agents. We demonstrate that PHA665752 reduces clonogenic survival of tumor cells with MET overexpression when combined with ionizing radiation and synergistically cooperates with ioniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 39 publications
7
51
0
Order By: Relevance
“…Therefore, targeting c-MET may exhibit a synergistic effect with chemotherapy or radiotherapy (24,25). The present findings are consistent with previous studies (26)(27)(28)(29). It has been previously reported that the combination therapy of the anti-HGF monoclonal antibody AMG102 with the cytotoxic agent temozolomide or docetaxel enhances the anti-tumor action of temozolomide and docetaxel against glioblastoma multiforme (30).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, targeting c-MET may exhibit a synergistic effect with chemotherapy or radiotherapy (24,25). The present findings are consistent with previous studies (26)(27)(28)(29). It has been previously reported that the combination therapy of the anti-HGF monoclonal antibody AMG102 with the cytotoxic agent temozolomide or docetaxel enhances the anti-tumor action of temozolomide and docetaxel against glioblastoma multiforme (30).…”
Section: Discussionsupporting
confidence: 82%
“…45) may play a role (12,14,15). Interestingly, we observed different expression profiles of p21 and p16 in our panel of cell lines following the combined treatment.…”
Section: Discussionmentioning
confidence: 62%
“…As activation of the MET receptor was reported to protect cancer cells from IR-induced cell death by enhancing DNA damage repair activity (14,17), here we examined the effect of MET inhibition by the small-molecule tyrosine kinase inhibitor tepotinib (MSC2156119; Merck) alone or along with IR in MET-overexpressing human gastric cancer cell lines GTL-16, MKN-45, SNU-638, SNU-5, and KATO-II. Importantly, we observed that exposure of cells to low doses of tepotinib alone or in combination with IR resulted in a significant decrease in cell proliferation as indicated by the loss of incorporation of BrdUrd ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bardelli and colleagues were the first to suggest that mutations in MET signaling lead to a substrate shift, that results in the activation of downstream effectors that are not activated by the wild-type receptor (9). This is further supported by the observation that MET mutants can couple with different signaling pathways, leading to diverse biologic consequences (10,(37)(38)(39)(40). These observations also support the findings by Graveel and colleagues who showed that knock-in mice expressing MET-mutated variants developed tumors of different histotypes (41).…”
Section: Discussionmentioning
confidence: 96%